2007
DOI: 10.1016/j.ijdevneu.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prenatal X‐irradiation on the developing cerebral cortex of rats. II: A quantitative assessment of glial cells in the somatosensory cortex

Abstract: The developing central nervous system is known to be highly vulnerable to X-irradiation. Although glial cells are involved in various brain functions, knowledge on the effects of X-irradiation on glial cells is limited. Therefore, the purpose of the present study was to evaluate the effects of prenatal X-irradiation on glial cells. Pregnant Wistar rats were exposed to X-irradiation at a dose of 1.0 Gy on day 15 of gestation. Their offspring were examined at 7 weeks of age. The forebrain weight of X-irradiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this vein, an improvement or enhancement of endothelial cell growth potentially improves CNS cell development and neural connections, which may be a possible therapeutic target to prevent development defects in the prenatal exposed subjects. On the other hand, it has been shown that a density of cortical neurons and astroglia was preserved in the postnatal rats following X-ray irradiation (1.0 Gy) despite a decrease in cortical thickness [45], [46]. These findings suggest that the local energy demand per unit volume was similar to that of non-exposed subjects.…”
Section: Discussionmentioning
confidence: 94%
“…In this vein, an improvement or enhancement of endothelial cell growth potentially improves CNS cell development and neural connections, which may be a possible therapeutic target to prevent development defects in the prenatal exposed subjects. On the other hand, it has been shown that a density of cortical neurons and astroglia was preserved in the postnatal rats following X-ray irradiation (1.0 Gy) despite a decrease in cortical thickness [45], [46]. These findings suggest that the local energy demand per unit volume was similar to that of non-exposed subjects.…”
Section: Discussionmentioning
confidence: 94%
“…To confirm the possibility that BDNF overexpression in hippocampal astrocytes produced anxiolytic-/antidepressant-like effects through neurogenesis-dependent and neurogenesis-independent mechanisms, we examined whether the ablation of neurogenesis through X-irradiation, which does not affect glial cells density or hippocampal morphology, 1, 26 blocked or attenuated the behavioral responses observed in lenti-BDNF mice in a new batch of animals (Figure 4; Supplementary Figure S5). …”
Section: Resultsmentioning
confidence: 99%
“…X-Ray irradiation can affect neurons and glial cells, although neurons are less sensitive to X-rays than are glial cells. A single-dose of X-ray irradiation with a D0 for X rays of 1.45 Gy does not damage nerve cells, especially oligodendrocytes, thereby promoting axon regeneration [ 94 , 95 ]. Kalderon and Fuks [ 96 ] found that X-rays can inhibit the death and degeneration of neurons and at least partially improve the recovery of motor function after spinal cord transection in rats.…”
Section: Reviewmentioning
confidence: 99%